PENGARUH DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP ODHA DI PUSKESMAS JUMPANDANG BARU KOTA MAKASSAR - Maria Ulfah Ashar (Universitas Sam Ratulangi, 2023)
Backgroud:Human Immunodeficiency Virus Acqured Immmunodeficiency Syndromme (HIV/AIDS) is growing rapidly and is one of the biggest challenges today despite efforts to control and suppress its transmission. AIDS is an infectious disease caused by infection from a virus called HIV, HIV / AIDS problem is a big problem that threatens Indonesia and many countries around the world. HIV/AIDS causes crises simultaneously, causing health crises, country-building crises, economic crises and humanitarian crises. Purpose :The purpose of this study was to determine the effect of family support on the quality of life of PLHIV at the Jumpandang Baru Health Center in Makassar City. The research method used is a quantitative method with a cross-sectional approach research design. The sampling technique in this study used a non-probability sampling method, namely accidental sampling. The number of samples in this study was 32 respondents. Result:The results of the somer's D test obtained a p value of 0.000 with a meaningfulness level of a 0.05 meaning a p value of < a which means that there is an influence of family support on the quality of life of PLHIV at the Jumpandang Baru Health Center, Makassar City with a correlation strength of 0.713 (strong). Conclusion:The conclusion of this study is that there is an influence of family support on the quality of life of PLHIV at the Jumpandang Baru Health Center in Makassar City and respondents who have a good quality of life on average have good family support. Advice for subsequent researchers is to be able to continue the research that has been carried out using different variables Keywords: Family Support, HIV/AIDS, Quality of Life